Regenerative fibroblasts derived from autologous skin tissue for the treatment of Sjögren’s syndrome: a case report - Ma, Zhao-Xia; Wu, Xing-Fei; Cao, Li; Jiao, Cheng-Yan; Ma, Dai-Ping; Zhao, Yun-Hui; Yang, Zhi-Xing; Hu, Min (Frontiers in Immunology, 2025)
BackgroundSjögren’s syndrome (SS) is a systemic autoimmune disease, with major symptoms including dry mouth and dry eyes, for which there is no effective treatment. Recent studies have demonstrated that mesenchymal stem cells (MSCs) are effective in the treatment of SS, but the efficacy of allogeneic MSCs is affected by variability among different cell donors, and they are easily cleared by the immune system of the recipient. Autologous MSCs are one of the ideal options for the treatment of SS; however, their function decreases with age. Regenerative fibroblast (rFib) is a type of new MSC obtained through chemical reprogramming technology from skin fibroblasts. In this study, we report the safety and efficacy of intravenous infusion of autologous rFib in a volunteer with SS.Case reportIn March 2021, the volunteer was diagnosed with SS due to positive anti-SSB antibodies, lymphocyte infiltration in the lip gland, dry eyes, and a large area of purpura in both lower limbs. From May 2021 to November 2022, she received allogeneic Umbilical cord mesenchymal stem cells (UCMSC) therapy (5.0 × 107 UCMSCs per time, totaling 10 infusions), but her condition did not improve. In May 2023, the rFib for the volunteer was prepared, meeting the quality standard of T/CSCB0003-2021 Human Mesenchymal Stem Cells. Between October 2023 and June 2024, the volunteer received a total of 12 intravenous transfusions of autologous rFib. After the treatments, the volunteer experienced no recurrence of purpura in both lower limbs. Symptoms of dry mouth, dry eyes, and fatigue were relieved. ESR, B lymphocytes, rheumatoid factor IgM, and IgA declined, while the proportion of NK cells increased, and most of the cytokines returned to normal levels. In vitro experiments showed that rFib could significantly inhibit the proliferation of T lymphocytes after PHA stimulation. No adverse effects were associated with the use of rFib in the volunteer during the clinical trial.SummaryThe results of this clinical trial indicate that intravenous injections of autologous rFib are both safe and effective for treating SS. Autologous rFib may be more suitable for treating autoimmune diseases than allogeneic MSCs.